Dynamics of DNA replication: an ultrastructural study - Philimonenko, Anatoly A; Jackson, Dean A; Hodný, Zdenek; Janácek, Jirí; Cook, Peter R; Hozák, Pavel (Journal of structural biology, 2004)
DNA replication in cells takes place in domains scattered throughout the nucleoplasm. We have characterized the dynamics of DNA synthesis in synchronized mid-S-phase HeLa cells. Saponin-permeabilized cells were allowed to elongate nascent DNA chains in presence of biotin-dUTP for 5, 15, and 30 min (a pulse experiment), or for 5 min followed by an incubation with unlabeled precursors for 10 or 25 min (a pulse-and-chase experiment). The replication foci were then identified in ultrathin sections using immunogold labeling of the incorporated biotin. Total number of particles per nucleus, total scanned area of the nucleus, size, shape, and gold particle number of each labeled cluster, and the density of clusters per nucleus were evaluated. We have demonstrated that as replication proceeds, the labeled sites increase in size up to 240 nm (30 min incorporation) while maintaining a broadly round shape. In pulse-and-chase experiments the labeled DNA was shown to spread to occupy DNA foci of approximately 400 nm in diameter. These results demonstrate that DNA replication is compartmentalized within cell nuclei at the level of DNA foci and support the view that the synthetic centers are spatially constrained while the chromatin loops are dynamic during DNA synthesis.
Keywords: Gold; vazebná místa; Cell Nucleus; Image Processing, Computer-Assisted; zlato; buněčné jádro; Saponins; chromatin; HeLa buňky; elektronová mikroskopie; saponiny; Time Factors; Chromatin; Binding Sites; počítačové zpracování obrazu; kinetika; lidé; Monte Carlo Method; HeLa Cells; Humans; Microscopy, Electron; metoda Monte Carlo; časové faktory; Biotin; replikace DNA; DNA; DNA Replication; Kinetics; biotin